Monetary Policy Transparency - Petra Geraats (Center for Economic Studies and ifo Institute (CESifo), 2014)
There has been a remarkable rise in the transparency of monetary policy during the last two decades. This paper provides an overview of the ways in which central banks have been providing more information about their monetary policymaking. Furthermore, it reviews the theoretical literature on monetary policy transparency and relevant empirical findings. The focus is on understanding two key developments, the notable increase in openness about macroeconomic prospects and the recent advance of forward policy guidance.
Keywords: E52; E58; 330; monetary policy; transparency; central banks